Therapeutic use of mini-scleral lenses in a patient with Graves’ ophthalmopathy - Harthan, Jennifer S. (2013)
Patients with Graves’ ophthalmopathy can be very challenging to manage secondary to the complex nature of their disease presentation. Patients may present with a variety of ocular findings including: lid retraction, periorbital and lid swelling, chemosis, conjunctival hyperemia, proptosis, optic neuropathy, restrictive myopathy, exposure keratopathy and/or keratoconjunctivitis sicca. Mini-scleral and scleral lens designs have been important in the management of irregular and regular corneas, and in the therapy of ocular surface diseases. We present here the case of a 48-year-old Caucasian male who had been diagnosed with Graves’ ophthalmopathy 13 years earlier. With significant ocular surface staining and over ten diopters of astigmatism, the patient had never been able to wear contact lenses comfortably. After being fit with the Mini-Scleral Design™ lenses, his vision improved to 20/25 OU, his ocular surface improved, and overall quality of vision increased.